2016
DOI: 10.18632/oncotarget.9928
|View full text |Cite
|
Sign up to set email alerts
|

Motility and stem cell properties induced by the epithelial-mesenchymal transition require destabilization of lipid rafts

Abstract: The Epithelial-Mesenchymal Transition (EMT) is a developmental program that provides cancer cells with the characteristics necessary for metastasis, including increased motility and stem cell properties. The cellular and molecular mechanisms underlying this process are not yet fully understood, hampering efforts to develop therapeutics. In recent years, it has become apparent that EMT is accompanied by wholesale changes in diverse signaling pathways that are initiated by proteins at the plasma membrane (PM). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 65 publications
0
40
0
Order By: Relevance
“…the fish oil component ω-3 docosahexaenoic acid, are robustly incorporated into cellular membranes, where they induce extensive remodelling of lipid compositions and biophysical properties, including increasing the stability of raft-like domains 67 . A study relating these effects to cell behaviour showed that ω-3 docosahexaenoic acid incorporation and concomitant increase in the stability of raft-like domains can repress stem cell properties and motility of breast cancer cells, by interfering with plasma membrane remodelling necessary for the process of epithelial–mesenchymal transition 139 .…”
Section: Mechanisms Of Domain Regulationmentioning
confidence: 99%
“…the fish oil component ω-3 docosahexaenoic acid, are robustly incorporated into cellular membranes, where they induce extensive remodelling of lipid compositions and biophysical properties, including increasing the stability of raft-like domains 67 . A study relating these effects to cell behaviour showed that ω-3 docosahexaenoic acid incorporation and concomitant increase in the stability of raft-like domains can repress stem cell properties and motility of breast cancer cells, by interfering with plasma membrane remodelling necessary for the process of epithelial–mesenchymal transition 139 .…”
Section: Mechanisms Of Domain Regulationmentioning
confidence: 99%
“…A model epithelial cell line that develops a discrete apical PM in culture on porous filter substrates (Madine-Darby Canine Kidney; MDCK) revealed clear remodeling of the lipidome during cellular polarization, which could be largely reversed by inducing an in vitro model of an epithelial-to-mesenchymal transition (EMT) 53 . These distinct lipid profiles are manifested in biophysical changes, as EMT induced by several independent means dramatically reduced the stability of domain formation in siolation GPMVs 73 . Notably, these effects could be partially reversed by altering cellular lipidomes via dietary lipids 73 .…”
Section: Lipidomic Complexity: the Known Unknownsmentioning
confidence: 99%
“…These distinct lipid profiles are manifested in biophysical changes, as EMT induced by several independent means dramatically reduced the stability of domain formation in siolation GPMVs 73 . Notably, these effects could be partially reversed by altering cellular lipidomes via dietary lipids 73 . EMT is thought to be involved in several cancer phenotypes, including migration and escape from apoptosis, so the observations that EMT is associated with distinctive lipidomic and biophysical characteristics that are tunable by dietary pertubations may have important translational implications for cancer diagnosis and treatment.…”
Section: Lipidomic Complexity: the Known Unknownsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of SNAIL significantly upregulates the expression of FOXC2 while overexpression of FOXC2 does not affect SNAIL levels (49,52) (Figure S8). This suggests that SNAIL functions as an upstream regulator of FOXC2.…”
Section: Overexpression Of Snail Is Insufficient To Initiate Emt In Amentioning
confidence: 99%